2010
DOI: 10.5014/ajot.64.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Drivers With Dementia and Outcomes of Becoming Lost While Driving

Abstract: Researchers of driving and dementia have reported that drivers with early Alzheimer's disease (AD) may continue to drive for extended periods of time, as long as their driving is evaluated or monitored. The earliest symptoms of AD are known to include loss of recent memory and the inability to recognize familiar environments. In an exploratory study, we examined 207 reports of lost drivers with dementia over 10 yr reported by newspapers and media. Seventy AD drivers were not found, 32 drivers were found dead, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
53
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 13 publications
1
53
1
Order By: Relevance
“…Adults with dementia are at an increased risk for unsafe driving and crashes (Fox, Bowden, Bashford, & Smith, 1997), and studies have shown that people with dementia often become lost when driving (Rowe, Feinglass, & Wiss, 2004;Silverstein, Flaherty, & Tobin, 2002). Evidence supports elevating our response to warning signs of cognitive impairment: The consequences of getting lost for people with dementia have been shown to include injury or death (Hunt, Brown, & Gilman, 2010).…”
mentioning
confidence: 99%
“…Adults with dementia are at an increased risk for unsafe driving and crashes (Fox, Bowden, Bashford, & Smith, 1997), and studies have shown that people with dementia often become lost when driving (Rowe, Feinglass, & Wiss, 2004;Silverstein, Flaherty, & Tobin, 2002). Evidence supports elevating our response to warning signs of cognitive impairment: The consequences of getting lost for people with dementia have been shown to include injury or death (Hunt, Brown, & Gilman, 2010).…”
mentioning
confidence: 99%
“…If the information from the navigator is given correctly, and in a timely and orderly way, drivers are not required to recall route-finding information; rather, they are able to focus on driving [17]. Nonetheless, Hunt et al [9] discouraged reliance on this strategy as navigators with poor navigational skills have been found to be a hazard because they can increase the drivers' cognitive load if misinformation is provided.…”
Section: Introductionmentioning
confidence: 99%
“…The potential consequences of drivers with AD becoming lost cannot be ignored; therefore, it is essential that potential solutions to help drivers with way-finding difficulties are explored in research [9,17]. Approximately 10-40% of drivers with mild AD have been reported as relying on their spouse or passengers to give them verbal prompts for navigation [15,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations